Power and terror Noam Chomsky in our times - Yamagami, Tetsujiro; Junkerman, John.; Chomsky, Noam.; Otsu, Koshiro; Hata, Takashi, 1953-; Imawano, Kiyoshiro; Siglo (Firm); First Run/Icarus Films (Brooklyn, NY : First Run/Icarus Films, 2002)
"Chomsky places the terrorist attacks of 9/11 in the context of American foreign intervention throughout the postwar decades--in Vietnam, Central America, the Middle East and elsewhere."--Container.
Linguistics and activism. Linguistics and politics -- Activism and political change.
DVD.
Featuring: Noam Chomsky.
Cinematographer, Koshiro Otsu ; editors, Takeshi Hata, John Junkerman ; music, Kiyoshiro Imawano.
MPAA rating: Not rated.
Special features: Bonus excerpts, profiles, about the book, and trailer gallery.
Keywords: Terrorism; September 11 Terrorist Attacks, 2001.; War on Terrorism, 2001-2009.; Terrorism -- Government policy -- United States; Documentary films